Recent Development of Benzimidazole‐Containing Antibacterial Agents. (10th March 2016) - Song, Di; Ma, Shutao
Abstract: Clinically significant antibiotic resistance is one of the greatest challenges of the twenty‐first century. However, new antibacterial agents are currently being developed at a much slower pace than our growing need for such drugs. Given their diverse biological activities and clinical applications, many bioactive heterocyclic compounds containing a benzimidazole nucleus have been the focus of interest for many researchers. The benzimidazole nucleus is a structural isostere of naturally occurring nucleotides. This advantage allows benzimidazoles to readily interact with the various biopolymers found in living systems. In view of this situation, much attention has been given to the exploration of benzimidazole‐based antibacterial agents, leading to the discovery of many new chemical entities with intriguing profiles. In this minireview we summarize novel benzimidazole derivatives active against various bacterial strains. In particular, we outline the relationship between the structures of variously modified benzimidazoles and their antibacterial activity. Abstract : Can′t resist higher efficacy : Antibiotic resistance is one of the greatest challenges faced in the clinic. As a constituent of many bioactive heterocyclic compounds with diverse activities and clinical applications, the benzimidazole nucleus has generated widespread interest. Herein we summarize novel benzimidazole derivatives that are active against various bacterial strains and reveal the relationship between the structures of differently modified benzimidazoles and their antibacterial activities.